Studi Analisis Konsep Maqāṣid Al-Syarī'ah Jasser Auda dan Relevansinya dengan Hukum Islam Kontemporer - Ramlah; Cantik Tri Rahajeng (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2025)
Maqāṣid al-Syarīʿah is one of the methodologies used for legal istinbat, with the main aim being based on the benefit of humanity. This goal includes protecting religion, reason, life, property and offspring. However, in its development, traditional maqāṣid al-Syarīʿah is considered less capable of providing solutions to contemporary Islamic legal problems, especially in facing increasingly advanced and complex developments, which require answers from Islamic legal products.This renewal of traditional maqāṣid al-Syarīʿah inspired the thinking of Jasser Auda, a leading figure in contemporary maqāṣid al-Syarīʿah. Therefore, the author is interested in raising this theme, because it is believed to be important for studying Jasser Auda's concept of maqāṣid al-Syarīʿah and its relevance to contemporary Islamic law. The research method used in this study is library research with a qualitative-descriptive approach. Data were obtained through an in-depth study of primary and secondary literature, which were then analyzed using the content analysis method. Jasser Auda's thoughts in maqāṣid al-Syarīʿah strive for the objectives of Allah SWT's law to be achieved evenly, with the basic principle of maqāṣid which is wholeness. The renewal in Islamic law that he promotes aims to realize comprehensive peace and welfare. One important reason for this renewal is the phenomenon of economic inequality, inequality of educational rights, and challenges to the implementation of ideal Islamic law. The relevance to contemporary Islamic law lies in the movement to improve the education system, inclusive economic growth, interactive-creative households, maintained diversity, and rejection of stagnation.